AGGRESSION IN RELATION TO SELF-ESTEEM, PEER PRESSURE, FAMILY ENVIRONMENT AND MEDIA VIOLENCE IN SCHOOL CHILDREN - Poonam (Innovative Research Thoughts, 2018)
World health organization (2002) defines, “Aggression, such as kicking, fighting and biting is a major concern for modern societies as the physical, emotional, cognitive and societal consequences of violent acts are serious, far reaching and long terms.” There are individual and environmental and situational characteristics might leads to aggressive behavior. Many factors may contribute to aggression including situations, Self-esteem, Peer Pressure, exposure to Media Violence and Family environment. The family environment is influenced by a number of factors like the nature of family constellation; number of children in the family; marital relationship between husband and wife; maternal (parent) employment; and socio-economic and religious background of the family. The present study (N=300) was conducted to examine the aggression in relation to family environment, peer pressure, self-esteem and media violence. Participant completed a questionnaire comprising Aggression scale, Self esteem scale, Peer pressure scale, Tv attitude scale and Family environment scale. The obtained data was analyzed for means comparison, Pearson’s product moment correlations and stepwise multiple Regression analyses. The study is useful to judge the Aggression of the School students which is an indicator of mental health. It evaluates Self-esteem, peer pressure, media violence and family environment will contribute substantially to the aggression.